Optimal Bidding Strategy of Generation Companies (GenCos) in Energy and Spinning Reserve Markets Using Linear Programming - Hassan Barati (Journal of Intelligent Procedures in Electrical Technology, 2011)
In this paper a new bidding strategy become modeling to day-ahead markets. The proposed algorithm is related to the point of view of a generation company (Genco) that its end is maximized its benefit as a participant in sale markets of active power and spinning reserve. In this method, hourly forecasted energy price (FEP) and forecasted reserve price (FRP) is used as a reference to model the possible and probable price strategies of Gencos. A bi-level optimization problem That first level, is used to maximize the individual Genco’s payoffs for obtaining the optimal offered quantity of Gencos. The second one, uses the results of the upper sub-problem and minimizes the consumer’s payment with regard to the technical and network constraints, which leads to the awarded generation of the Gencos. In this paper use of the game theory in exist optimization model. The paper proposes a linear programming approach. A six bus system is employed to illustrate the application of the proposed method and to show its high precision and capabilities.